Mortality after remote surgery for benign gastroduodenal disease. Issue 5 (November 1995) - Staël von Holstein, C C; Anderson, H; Eriksson, S B; Huldt, B
Abstract : Mortality was studied after partial gastrectomy in a cohort of 1575 patients operated on because of benign gastroduodenal disease 29 to 59 years ago. The final status was confirmed in all but 8.4% of the cohort. At the close of the study 78% of the traced population were dead. Overall mortality was significantly higher than in the general population of southern Sweden (standardised mortality ratio = 1.10; 95% confidence intervals 1.03 to 1.17). Excess deaths resulted from neoplasms in the stomach, pancreas, male genital organs, and respiratory organs, as well as from respiratory diseases and suicide. Patients operated on before the age of 45 had a 60% increase in overall mortality during the first 19 years after surgery, mainly because of cardiovascular disease and suicide, whereas among those operated on after this age mortality was comparable to that in the reference population. The 75% increased death rate in cardiovascular disease during the first 19 years after surgery in patients operated on at young age, dramatically decreased during the years thereafter. An increased risk of death caused by malignancy was apparent more than 20 years postoperatively, irrespective of age at surgery. Excess deaths resulting from gastrointestinal malignancies, mainly gastric and pancreatic carcinoma, outnumbered the increased number of deaths resulting from cancer in the respiratory organs.